ANALISIS STRATEGI BANK SYARIAH DALAM MENINGKATKAN PEMBIAYAAN BAGI PELAKU USAHA KECIL MENENGAH (UKM): INNER SHARIA BANK STRATEGY ANALYSIS INCREASING FINANCING FOR SMALL AND MEDIUM ENTERPRISES (UKM) - Nadhea Jelita Pertiwi; Muhammad Iqbal Fasa; Is Susanto (PT. Intelek Cendikiawan Nusantara, 2024)
In the Indonesian economy, Micro, Small, and Medium Enterprises (MSMEs) constitute the largest group of businesses. Additionally, this sector has proven to be resilient against various economic crises. Therefore, strengthening the MSME sector is crucial, as it involves many stakeholders and plays a significant role in labor absorption. The development of MSMEs can create more jobs, improve the welfare of workers in the labor force, reduce unemployment, and ultimately contribute to poverty alleviation. The criteria for businesses that fall under MSMEs have been regulated under legal frameworks based on national laws. This study aims to explore the role of Islamic banking in supporting Micro, Small, and Medium Enterprises (MSMEs) at Bank Syariah Indonesia (BSI). The research employs data collection techniques to examine how poverty alleviation can be achieved, in part, by breaking the cycle of poverty itself. One approach to doing so is by providing broad access to financing sources for MSMEs, which is facilitated by financial institutions, particularly Islamic banks. Islamic banks are financial institutions that act as mediators in the economy by offering savings, financing, and other financial services based on the principles of trust derived from the Qur'an and Hadith. The goal of this research is to identify the strategies employed by Islamic banks to enhance financing for small and medium-sized enterprises (SMEs). Using a qualitative research method, this study aims to provide a clearer understanding of how Islamic banks can drive the growth of MSMEs and contribute to poverty reduction and social equity. aims to highlight.